Mobile Remote Content Feed Editing in Content Management System - Ganapathy, Apoorva (Engineering International, 2019)
Mobile content editing in a content management system is the way and manner in which web or electronic content is edited, added, removed, or modified. The internet is the network of affiliated websites, while a website is an interconnection between web pages online. This work explains how the websites are created and authored using the HTML method and the various web authoring tools. It presents the reader with the benefits of using web authoring in web building.